Global Economic Prospects : Financial Market Outlook, March 2013 - Aykut, Dilek; Kim, Eung Ju (World Bank, Washington, DC, 2015)
Global financial conditions have improved substantially since July 2012, a reflection of the cumulative steps taken by high-income countries' central banks. Gross capital flows to developing countries, which weakened in mid-2012 due to Euro area turmoil, bounced back in the second half of the year. Foreign direct investment (FDI) inflows to developing countries are expected to have declined slightly in 2012 following increased uncertainty in global financial markets. Gross capital flows have remained strong so far in 2013, with January and February flows 47 percent higher than in the same period in 2012. The level of net capital flows going to developing countries is set to rise through 2015.